Informal sector misallocation - Bernabe Lopez-Martin (Banco de México, 2016)
A quantitative framework of firm dynamics is developed where the size of the informal sector is determined by financial constraints and the burden of taxation. Improving access to credit for formal sector firms increases aggregate TFP and output while reducing the size of the informal sector. Introducing size-dependent taxes reduces the gains from financial development as they incentivize firms to produce at a relatively limited scale. The aggregate effects of eliminating formal sector registration costs are positive but modest relative to previous theoretical models and the gains generated by financial development, and consistent with empirical evidence based on micro-level data.
Keywords: E26; L11; O11; O17; O40; 330; informal sector; misallocation; aggregate productivity; financial constraints; size-dependent taxes